Strategi Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu dalam Meningkatkan Kepatuhan Pelaporan Laporan Kinerja Penanaman Modal dalam Negeri Kota Surabaya - Octaverina, Shelina Rintan; M, Meirinawati; Fanida, Eva Hany; Oktariyanda, Trenda Aktiva (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the strategy of the Surabaya City Investment and One-Stop Integrated Service Office (DPMPTSP) in improving LKPM reporting compliance for domestic business actors (PMDN). This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through in-depth interviews, observation, and documentation. Research informants consist of Surabaya City DPMPTSP employees and PMDN business actors. Data analysis is carried out using SWOT analysis through the preparation of IFAS and EFAS matrices to identify strengths, weaknesses, opportunities, and threats that affect LKPM reporting compliance. The results show that the Surabaya City DPMPTSP has strengths in the form of intensive mentoring programs through Lapis-Lupis and TAKON SOBAT services, human resource competency, and support for service facilities and infrastructure. The weaknesses faced include limited human resources, technical constraints in the OSS-RBA system, and a suboptimal reporting reminder system. In terms of opportunities, the enactment of Government Regulation Number 28 of 2025, support from the Surabaya City Government, and the potential for strengthening the communication system are factors that support increased compliance with LKPM reporting. Meanwhile, threats stem from low awareness among some business actors, limited coordination with company PICs, and disruptions to the OSS-RBA system. Based on the results of the IFAS and EFAS analysis, the strategic position of the Surabaya City DPMPTSP is in the Strength–Opportunity (SO) quadrant.